Detecting Earnings Management And Earnings Manipulation In Indonesia: A Panel Data Analysis - Tasya Febby Yolanda; Masiyah Kholmi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to measure the quality of profits in non-financial sector companies in Indonesia regarding the extent to which the Company's financial reports are trustworthy to stakeholders. In this research, discretionary accruals are an indicator for measuring earnings manipulation, and non-discretionary accruals are an indicator for measuring earnings management. Secondary data is from annual reports of non-financial sector companies on IDX in 2020-2022. The sample for this research is non-financial sector companies, including the raw materials, manufacturing, and service sectors. Our research uses a modified Jones Model to estimate earnings management and earnings manipulation. The data analysis technique uses panel data regression. The research results show that the value aspect of discretionary accruals significantly influences total accruals. In contrast, the value of non-discretionary accruals does not significantly impact total accruals. This research is expected to help auditors, users of financial reports, and accounting standards bodies identify companies that fraud.